2013
DOI: 10.1021/jf400192v
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin Inhibits Tumor Growth through Downregulation of Extracellular Signal-Regulated Kinase and Akt in Vitro and in Vivo in Human Ovarian Cancer Cells

Abstract: Anticancer activity of silibinin, a flavonoid, has been demonstrated in various cancer cell types. However, the underlying mechanisms were not elucidated in human ovarian cancer cells. The present study was undertaken to examine the effect of silibinin in vitro and in vivo on tumor growth in human ovarian cancer cells. Silibinin decreased cell viability in a dose- and time-dependent manner. Silibinin caused an increase in reactive oxygen species (ROS) generation, and the silibinin-induced cell death was preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…The Akt signaling pathway also played a pivotal role in cell proliferation and cell apoptosis by transferring the signals to prevent apoptosis [37], [38]. Huang et al reported that the abnormalities of Akt signaling in ovarian cancer may be used to predict patient outcomes [39].…”
Section: Resultsmentioning
confidence: 99%
“…The Akt signaling pathway also played a pivotal role in cell proliferation and cell apoptosis by transferring the signals to prevent apoptosis [37], [38]. Huang et al reported that the abnormalities of Akt signaling in ovarian cancer may be used to predict patient outcomes [39].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have shown that downregulation of ERK and Akt is involved in flavonoid-induced apoptosis in various cancer cells (Jeong et al, 2009;Cho et al, 2013). However, the underlying mechanism of such a downregulation of kinases remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Several types of flavonoids have been identified as having antiproliferative efficacy in various cancers, including silymarin, genistein, quercetin, daidzein, luteolin, kaempferol, apigenin, and epigallocatechin 3-gallate [11, 12]. These aforementioned compounds have been reported to have anticancer and preventive effects against prostate [13], colorectal [14], breast [15], thyroid [16], lung [17], and ovarian [18] cancers, among others [1921]. Their chemopreventive efficacy is mediated by (1) inhibiting the development of new cancer cells; (2) preventing carcinogens from reaching their activation sites; and (3) decreasing the toxicity of certain compounds by inhibiting their metabolism [2224].…”
Section: Flavonoids In Cancer Chemopreventionmentioning
confidence: 99%